Contested Notions of National Identity, Ethnic Movements And Democratization in Iran - Yesiltas, Ozum (Studies of Transition States and Societies, 2016)
Since the Constitutional Revolution of 1906, successive regimes in Iran promoted competing conceptions of Iranian national identity. However, the policy of promoting nationalism as a state-sponsored ideology that excludes Iran’s ethnic and religious diversity remained unchanged. Competing discourses around nation building and identity strikingly intersect with the struggle for democratization in Iran. Since the Islamic Revolution, the pro-democracy movement in the country takes place on two fronts: the confrontation between the conservatives and the reformists, and the challenge posed by the ethnic movements towards the official denial of the ethnic and religious diversity of Iran. This article argues that be they reformist or conservative, successive governments in Iran have refused to recognize the multi-ethnic structure of Iranian society and the legitimate rights of the ethnic groups. Therefore, a regime change would be unlikely to alter the social and political status of ethnic and religious minorities unless the ethnic movements and the pro-democracy opposition collaborate. Formation of a common discourse on the question of ‘Iranianness’ is the primary condition for this to be accomplished.